RENCANA ANGGARAN BIAYA DAN EVALUASI E-PROCUREMENT PADA PEMBANGUNAN GEDUNG ASRAMA DI TANGERANG SELATAN - Irfan Nanda Pratama; Ninik Paryati; Rika Sylviana (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The Cost Budget Plan (RAB) is one of the main processes in a project because it is the basis for making a financing system offer and the budget framework that will be issued. The Cost Budget Plan (RAB) is needed to calculate a building or project with the amount of costs required for materials, wages and other costs related to building implementation. The Student Dormitory Building Construction Work Package in Bintaro was announced on the LPSE website of the Ministry of Finance. The Dormitory Building stands on a total land area of ±212,222m². Meanwhile, what will be built as a Student Dormitory building with a design area of ±3,647m² with a total of 8 Dormitory floors. From the calculation results, it is known that the recapitulation of the Cost Budget Plan (RAB) is Rp. 67,619,783,891 including 12% VAT with the largest work value being on the 2nd floor structure work with a value of Rp. 7,309,075,651. The advantage of e-Procurement is that it is very helpful for construction service providers to participate in each selection stage because it is not limited by distance and all processes are carried out online. However, in practice, this e-procurement system still relies on offline face-to-face meetings, such as the Aanwijzing stage, and is often found in the final negotiation stage. This can raise suspicion among every tender participant